Congenital myasthenic syndrome caused by mutations in DPAGT. - Klein, A; Robb, S; Rushing, E; Liu, W; Belaya, K; Beeson, D (2015)
Congenital myasthenic syndromes with prominent limb girdle involvement are an important differential diagnosis for congenital myopathies because of the therapeutic considerations. We present a case where accurate diagnosis was delayed for many years. Fluctuations of weakness were misinterpreted as effects of alternative treatments. Weakness was generalised, most prominently in the arms. Fatigability was more prominent in less affected muscles revealed by a positive Simpson test. Stimulation single fibre electromyography confirmed the suspected neuromuscular transmission defect. The marked response to pyridostigmine and cognitive impairment pointed to a myasthenic syndrome due to impaired glycosylation. Two mutations in trans were found in DPAGT1, the gene coding for dolichyl-phosphate N-acetylglucosaminephosphotransferase, one novel, the other previously reported in a rare form of congenital disorder of glycosylation. Gene expression studies revealed that both mutations reduce DPAGT1 expression. Phenotypic features not previously described for DPAGT1 CMS included restricted ocular abduction and long finger flexor contractures.